PELATIHAN PENGGUNAAN APLIKASI CANVA SEBAGAI MEDIA PEMBUATAN BUKU CERITA BERGAMBAR (PICTBOOK) DI KOMUNITAS GURU KREATIF SUKA MENULIS KALIMANTAN TIMUR - Siti Lailiyah; Amelia Yusnita; Yulindawati (Politeknik Negeri Sriwijaya, 2023)
The Canva application is a platform used for designing and is useful for honing creativity, one example of a design that can be made is an illustration. Picture story books are learning media that can improve children's reading interests and develop children's language skills. The Creative Teacher Community Likes to Write in East Kalimantan is very active in writing story books, especially children's story books, but to make illustrated illustrations very minimal, the community usually uses the services of an illustrator to help make the illustrations, and sometimes the illustrations that are made don't quite match the wishes of the author. The East Kalimantan Creative Teachers Like Writing Community has collaborated with STMIK Lecturer Widya Cipta Dharma to provide training to the community to increase knowledge about making illustrations, especially for picture storybooks. This training is a community service activity, the method used is an applied method that starts with a pretest to an assessment of the participant's ability to make picture storybooks. The training, which started from the opening to the closing, ran smoothly. This training is hoped to become a routine agenda for STMIK Widya Cipta Dharma.